A comparison between zinc sulfate and chlorhexidine gluconate mouthwashes in the prevention of chemotherapy-induced oral mucositis - Mehdipour, M. (Tehran University of Medical Sciences, 2011)
BACKGROUND AND THE PURPOSE OF THE STUDY: Patients undergoing high-dose chemotherapy for hematological malignancies are susceptible to development of oral mucositis, and no effective modality has been reported for its prophylaxis and treatment. The aim of this study was to evaluate the effectiveness of zinc mouthwash on chemotherapy-induced oral mucositis lesions. METHODS: In this double-blind randomized trial, patients under chemotherapy for acute leukemia were divided into two test and control groups of 15 patients each. The groups were homogeneous with respect to medical history, tumor characteristics, and therapeutic details. The test group received 10ml 0.2% zinc sulfate mouthwash, and the control group received 10ml 0.2% chlorhexidine gluconate mouthwash, twice a day for a period of two weeks. Spijkervet scale was used to grade the severity of mucositis at every other week during eight weeks. The severity scores were analyzed with repeated measure ANOVA using SPSS 13.0 computer software. RESULTS: Mean severity scores were generally lower in the test group compared to the controls at all four time intervals evaluated; but only, the differences in weeks of 2 and 3 were statistically significant (P=0.025). CONCLUSION: Zinc mouthwash used in conjunction with chemotherapy may reduce the severity of oral mucositis lesions in patients with leukaemia.